PENGARUH MEDIA LECTORA TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATERI PERANGKAT LUNAK MPEMBUAT GRAFIS DI SMA NEGERI 1 RAO - Taufiq Hidayat1 (Universitas PGRI Sumatera Barat, 2021)
This research was conducted because of SMA 1 Rao was already have adequate facilities to support learning process like library and computer room. However, in fact, the facility had not been used maximally in the learning process, especially in learning process of Information Communication and Technology (ICT) lesson. Some teachers also still used speech method and conversional media. In line with the problems, this research aimed to find out the effect of Lectora media as a learning media towards the students’ learning achievement in graphics software material at SMA Negeri 1 Rao. This research used a quantitative approach, and the subject of this research was SMA Negeri 1 Rao, the experimental class was XII.IPA-3 and XII.IPA-4 as control class. In data collection techniques, the researcher used questionnaires and tests. Questionnaires were distributed in the experimental class which used lectora media, and control class with no questionnaire because they did not use lectora media.The result of research showed that the effect of lectora media towards the learning achievement was the magnitude of effect of 5.1%, while the percentage between experiment class and control class were increasement of percentage of 42.5%, thus it was proven that the effect of lectora media to students' learning achievement was better than who did not use the lactor media.